Divergent membrane properties of mouse cochlear glial cells around hearing onset. Issue 2 (25th October 2020) - Smith, Katie E.; Murphy, Phoebe; Jagger, Daniel J.
Abstract: Spiral ganglion neurons (SGNs) are the primary afferent neurons of the auditory system, and together with their attendant glia, form the auditory nerve. Within the cochlea, satellite glial cells (SGCs) encapsulate the cell body of SGNs, whereas Schwann cells (SCs) wrap their peripherally‐ and centrally‐directed neurites. Despite their likely importance in auditory nerve function and homeostasis, the physiological properties of auditory glial cells have evaded description. Here, we characterized the voltage‐activated membrane currents of glial cells from the mouse cochlea. We identified a prominent weak inwardly rectifying current in SGCs within cochlear slice preparations (postnatal day P5‐P6), which was also present in presumptive SGCs within dissociated cultures prepared from the cochleae of hearing mice (P14‐P15). Pharmacological block by Ba 2+ and desipramine suggested that channels belonging to the Kir4 family mediated the weak inwardly rectifying current, and post hoc immunofluorescence implicated the involvement of Kir4.1 subunits. Additional electrophysiological profiles were identified for glial cells within dissociated cultures, suggesting that glial subtypes may have specific membrane properties to support distinct physiological roles. Immunofluorescence using fixed cochlear sections revealed that although Kir4.1 is restricted to SGCs after the onset of hearing, these channels are more widely distributed within the glial population earlier in postnatal development (i.e., within both SGCs and SCs). The decrease in Kir4.1 immunofluorescence during SC maturation was coincident with a reduction of Sox2 expression and advancing neurite myelination. The data suggest a diversification of glial properties occurs in preparation for sound‐driven activity in the auditory nerve. Abstract : Mouse cochlear glial cells have region‐specific membrane properties. Within dissociated cultures, satellite glial cells (SGCs) have large weak inwardly rectifying currents, likely mediated by Kir4.1 channels. Presumptive Schwann cells lack these currents. Soon after birth, Kir4.1 subunits appear in both glial subtypes, but become restricted to SGCs around hearing onset.